Technology - Finan, Catherine C. (Minneapolis : Bearport Publishing Company, 2021)
"Trains that zip passengers along while hovering just above the ground, doctors that can print human body parts, and a gadget that cleans your dirty dishes while making soil for your plants. Sounds like science fiction, right? But it's all real technology! For as long as we've been around, humans have created stupendous solutions to our peskiest problems. Discover the extreme facts about technology in this kooky book"-- Provided by publisher
Keywords: Juvenile works; Science Juvenile literature